PRODUKTIVITAS BONGKAR MUAT MODA ANGKUTAN BARANG di PERGUDANGAN KOTA PAREPARE - Hidayat, Rahmat; Hakzah Hakzah; Andi Bustan Didi (Jurnal Teknik Sipil dan Arsitektur, 2026)
Logistics operations, particularly loading and unloading (L/U) activities within warehouses, constitute critical components of the supply chain. Parepare City, a logistics hub in Indonesia, faces operational challenges including prolonged waiting times and facility constraints, leading to goods congestion and diminished L/U productivity. This study aims to characterize warehouse facilities and freight transport modes while quantitatively measuring cargo handling productivity. Employing a mixed-methods approach, data were collected via field observations (including timed L/U cycles), questionnaires, and documentation across four mechanized warehouses (three commercial, one steel material facility). Multiple linear regression analysis (SPSS v.26) was applied. Field measurements revealed peak productivity at the steel warehouse (51 pieces/minute, negligible waiting time), contrasting with significant variability and extended waiting periods (e.g., 119 minutes) observed in commercial warehouses. Regression analysis identified the quantity of goods (X1), equipment performance (X2), and L/U time (X3) as statistically significant predictors of productivity (Y). The strongest model (RÂ² = 79.5%) was derived for the steel warehouse. The study concludes that strategic investment in mechanical handling equipment and enhanced scheduling protocols are imperative to mitigate waiting times and elevate overall productivity. Its novelty resides in addressing a significant gap in the regional logistics literature through an empirical focus on Parepare's unique warehouse operations.